Sample size calculation in clinical research - Ranganathan, Priya; Deo, Vishal; Pramesh, C. S. (Perspectives in clinical research, 2024)
Abstract Calculation of sample size is an essential part of research study design since it affects the reliability and feasibility of the research study. In this article, we look at the principles of sample size calculation for different types of research studies.